Multimaterial 3D Printing Techology - Yang, Jiquan, author 651666; Li, Na, author 651667; Shi, Jianping, author 651668; Tang, Wenlai, author 651669; Zhang, Gang, author 592845; Zhang, Feng, author 651670; ScienceDirect (Online service) 7722 (London : Academic Press, 2021)
Multi-material 3D Printing Technology introduces the first models for complex construction and manufacturing using a multi-material 3D printer. The book also explains the advantages that these innovative models provide at various points of the manufacturing supply chain. Innovations in fields such as medicine and aerospace are seeing 3D printing applied to problems that require the technology to develop beyond its traditional definitions. This groundbreaking book provides broad coverage of the theory behind this emerging technology, and the technical details required for readers to investigate these methods for themselves. In addition to describing new models for application of this technology, this book also systematically summarizes the historical models, materials and relevant technologies that are important in multi-material 3D printing.